2019
DOI: 10.12688/wellcomeopenres.15151.1
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death among homeless people: a population-based cross-sectional study of linked hospitalisation and mortality data in England.

Abstract: Background: Homelessness has increased by 165% since 2010 in England, with evidence from many settings that those affected experience high levels of mortality. In this paper we examine the contribution of different causes of death to overall mortality in homeless people recently admitted to hospitals in England with specialist integrated homeless health and care (SIHHC) schemes. Methods: We undertook an analysis of linked hospital admission records and mortality data for people attending any one of 17 SIHHC sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 12 publications
(11 reference statements)
1
109
0
Order By: Relevance
“…6 The need for monitoring of health outcomes and collection of routine surveillance data to help implement this is stressed. 3,5 A recent national study in mainstream general practice found that patients with a higher number of LTCs were found to be at increased risk of missing GP appointments, especially patients with diagnosed mental health conditions.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…6 The need for monitoring of health outcomes and collection of routine surveillance data to help implement this is stressed. 3,5 A recent national study in mainstream general practice found that patients with a higher number of LTCs were found to be at increased risk of missing GP appointments, especially patients with diagnosed mental health conditions.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Older persons (>50) experiencing homelessness have multiple health problems that remain unaddressed by healthcare services, often lack social support and do not explicitly express their own healthcare needs (van Dongen et al, ), resulting in higher use of acute care. The excess mortality associated with considerable social exclusion, such as homelessness, is extreme (Aldridge et al, ; Fazel, Geddes, & Kushel, ; Slockers, Nusselder, Rietjens, & van Beeck, ), that is, the mortality rate is nearly eight times higher than the average for men and 12 times higher for women (Aldridge et al, ), with an average age for death at 52 years.…”
Section: Introductionmentioning
confidence: 99%
“…This global burden of homelessness has critical implications for health policymaking and practice. In homelessness, the rate of mortality is nearly eight times higher than the average for men and 12 times higher for women, with an average age for death at 52 years (Aldridge et al, 2019(Aldridge et al, , 2018. This can be attributable to the fact that homeless individuals experience enormous health inequalities and have a higher prevalence of various medical conditions (Omerov et al, 2020).…”
Section: Introductionmentioning
confidence: 99%